Evaluating the performances of surface drainage efficiency in left bank outfall drain (LBOD) at Sanghar component, Sindh - VistroR , Rahim Bux; Mangrio, Munir Ahmed; Siyal, Abdul Ghafoor; Abbasi, Abdul Qudoos; Ahpun, Aijiz Ali; Soothar, Rajesh Kumar (Journal of Pure and Applied Agriculture, 2023)
This study was conducted at Sanghar component of left bank outfall drain (LBOD) project for evaluating the efficiency of drainage system in terms of operation and maintenance. Makhi Branch Drain and Sanghar-1R drain were selected and their allied tubewells along with disposal channels for the system evaluation. The results showed that the operational efficiency of drainage tubewells was found very poor. The average operational efficiency was calculated as 24%, whereas the value of coefficient of variation of tubewell operational efficiency is greater than 0.30 and leads up to 0.90, which shows high variability in operation. The disposal channels are 88% efficient in terms of carrying the tubewell discharge into the main drain. This percentage is considered high in relation to the shorter length. Therefore,